2015
DOI: 10.1111/exd.12634
|View full text |Cite
|
Sign up to set email alerts
|

Nickel acts as an adjuvant during cobalt sensitization

Abstract: Metal allergy is the most frequent form of contact allergy with nickel and cobalt being the main culprits. Typically, exposure comes from metal‐alloys where nickel and cobalt co‐exist. Importantly, very little is known about how co‐exposure to nickel and cobalt affects the immune system. We investigated these effects by using a recently developed mouse model. Mice were epicutaneously sensitized with i) nickel alone, ii) nickel in the presence of cobalt, iii) cobalt alone, or iv) cobalt in the presence of nicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 10 publications
(7 reference statements)
0
24
0
Order By: Relevance
“…Despite the high prevalence of concomitant nickel and cobalt allergy (63), it has been shown that human nickel-specific T cells do not cross-react with cobalt (42, 57). We found that nickel induced more local inflammation than cobalt in mice exposed to only the individual metal during challenge, indicating that nickel is a more potent adjuvant than cobalt (62). Interestingly, it has been shown that chromium [Cr(VI)] is more cytotoxic and that it accumulates more within keratinocytes than nickel and cobalt (64,65).…”
Section: The Effect On the Immune Responsementioning
confidence: 88%
See 2 more Smart Citations
“…Despite the high prevalence of concomitant nickel and cobalt allergy (63), it has been shown that human nickel-specific T cells do not cross-react with cobalt (42, 57). We found that nickel induced more local inflammation than cobalt in mice exposed to only the individual metal during challenge, indicating that nickel is a more potent adjuvant than cobalt (62). Interestingly, it has been shown that chromium [Cr(VI)] is more cytotoxic and that it accumulates more within keratinocytes than nickel and cobalt (64,65).…”
Section: The Effect On the Immune Responsementioning
confidence: 88%
“…Addition of 1% NiCl 2 during sensitization with 10% CoCl 2 led to a strong increase in the challenge response to 10% CoCl 2 as compared with the challenge response in mice sensitized with 10% CoCl 2 alone, as measured by ear thickness and proliferation of B and T cells ; that is, a synergistic or – in this case – ‘adjuvant’ effect was noted. In contrast, addition of 1% CoCl 2 to 10% NiCl 2 during the sensitization response led to only a minor increase in CD8 + T cell proliferation following challenge with 10% NiCl 2 as compared with mice sensitized with 10% NiCl 2 alone . T cell cross‐reactivity does not seem to explain these observations.…”
Section: Effects Of Mixing Contact Allergensmentioning
confidence: 90%
See 1 more Smart Citation
“…The moderately increased response to DNFB and cinnamal in ft/ft mice is probably mediated by steady‐state skin inflammation, as both allergens are likely to penetrate skin with and without filaggrin proteins and degradation products. Co‐exposure to mixtures of allergens and irritants increases the immune response, so, similarly, we suspect that the existing inflammation in ft/ft skin could reduce the inflammatory threshold for DNFB and cinnamal, and thereby explain the moderately enhanced responses to these allergens …”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of her cobalt and palladium reactions is uncertain. Many nickel‐allergic patients are co‐sensitized to cobalt and cross‐react with palladium . Palladium and nickel both belong to Group VIII of the periodic table .…”
Section: Discussionmentioning
confidence: 99%